The Evaluation of a Technology-Embedded Solar Energy STEM (SESTEM) Module: A Pilot Implementation of Modern Teaching Tool for Diploma Science Students - Supian, F. L.; Tho, S. W.; Wong, Y. Y.; Mohd Azmi, M. S.; Hosman, N. J.; Ratnawulan, R.; Al Naim, A. F. (Jurnal Pendidikan IPA Indonesia, 2023)
Utilising an excellent teaching tool is vital for students' education nowadays.  In contrast to the traditional teaching way, Technology-Embedded Solar Energy STEM (SESTEM) module was created as a modern teaching tool for physics subject. In order to develop and evaluate the students’ perception towards the complete SESTEM module, developmental research and technology acceptance model (TAM) were applied in this research study. 52 randomly selected diploma students from Sultan Idris Education University (UPSI) were involved as respondents in this work. After the development of the SESTEM module using the analysis, design, development, implementation and evaluation (ADDIE) model, the perceptions of students as respondents towards this module were evaluated based on the TAM via questionnaire. Based on the responses from the respondents, the majority of the respondents demonstrated positive attitudes and behaviour intention, as well as agreed that the SESTEM module was useful as a teaching tool. Besides, the respondents showed a positive technological acceptance towards SESTEM module. The respondents' acceptance was contingent on the employment of technology for educational purposes in the future. Consequently, SESTEM module could be utilised by educators as a contemporary tool for enhancing student learning for future benefits.